PENILAIAN KINERJA BERDASARKAN BALANCED SCORECARD PADA BADAN PENANAMAN MODAL DAN PERIJINAN DAERAH KABUPATEN TABANAN - Nugrahini, Ida Ayu Putu; Dwi Ratnadi, Ni Made; Asri Dwija Putri, I G A Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.04.TAHUN 2016, 2016)
Public sector organizations that carry out the investment and licensing functions area is Investment Board and the Regional Licensing (BPMPD). The research objective was to determine the performance BPMPD Tabanan based on four perspectives Balanced scorecard by using non quantitative statistics. Performance of the financial perspective, internal business process, customer, and learning and growth each assessed through Value For Money (VFM), measurement of infrastructure capacity, Community Satisfaction Index, customer satisfaction and employee productivity. Results of the analysis is based on the balanced scorecard measurement showed that the performance BPMPD overall Tabanan are on the qualification being the success rate is quite successful.
Keywords: performance of the financial perspective, internal business processes, customers, growth and learning.